2022
DOI: 10.3390/jcm11195813
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Reliability of Perforator Flaps in the Reconstruction of Hidradenitis Suppurativa Defects: A Systemic Review and Meta-Analysis

Abstract: Introduction: Hidradenitis suppurativa (HS) is a common and debilitating disease, in which the only effective treatment involves a wide excision of the affected skin. Secondary wound healing and skin grafting are two well-known options for managing these defects, but perforator flaps provide a new therapeutic alternative by ensuring reconstructions of large defects, reducing donor site morbidity, and enhancing functional recovery. The aim of this study was to achieve a systematic review of perforator flaps use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
1
6
0
1
Order By: Relevance
“…Specifically, they reported complication rates of 17.1% for TDAP flaps and 16.7% for IAAP flaps. 33 All studies above confirm our team's findings: surgical management for Hurley grade 3 axillary HS by radical excision offers excellent results with a low recurrence rate (a single patient in our series). A plethora of solutions exists for managing the resulting defect.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Specifically, they reported complication rates of 17.1% for TDAP flaps and 16.7% for IAAP flaps. 33 All studies above confirm our team's findings: surgical management for Hurley grade 3 axillary HS by radical excision offers excellent results with a low recurrence rate (a single patient in our series). A plethora of solutions exists for managing the resulting defect.…”
Section: Discussionsupporting
confidence: 86%
“…Although they require longer operative times and greater surgical skills, they offer shorter postoperative healing periods and deliver excellent functional and aesthetic outcomes for the upper limb. 33,37,49 To our knowledge, our study is the first to directly compare the islanded TDAP flap and propeller IAAP flap for axillary reconstruction after wide local excision in patients with stage 3 HS. All the flaps in our study were performed by a single academic surgeon (N.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For what concerns postoperative complications after reconstruction with perforator flaps, Vaillant et al (2022), published a systematic review reporting an overall complication rate as high as 15.1%. Moreover, in their study, Lafaye et al (2022) found a partial flap necrosis rate of 28.4%.…”
Section: Discussionmentioning
confidence: 99%
“…As local flaps bear the risk of containing HS affected skin, reconstruction with skin flaps should only be performed after wide surgical excisions [ 228 ]. Currently, there is a large number of different skin flaps that have been described for HS reconstruction and frequently used flaps are lateral thoracic island fasciocutaneous flaps [ 229 ], Limberg transposition flaps [ 230 ], fasciocutaneous perforator-based flaps [ 231 ], myocutaneous flaps [ 232 , 233 ] and thoracodorsal artery perforator flaps [ 234 , 235 ].…”
Section: Treatmentmentioning
confidence: 99%